AKOMODASI DAN KONTESTASI RUANG BUDAYA DI UDARA: KASUS SIARAN BUDAYA DI RRI KENDARI, SULAWESI TENGGARA - Baskara, Benny (Studi Budaya Nusantara, 2018)
Abstract Radio Republik Indonesia (RRI) as state-owned radio station creates a special channel for cultural programs from various ethnic groups in Indonesia in Programme 4. The establishment of Programme 4 as the special channel for cultural programs is a form of accommodation from Indonesian government toward various ethnic groups in Indonesia, including in RRI Kendari as a branch of RRI in Southeast Sulawesi Province. This paper will describe the accommodation and contestation of cultural programs in Programme 4 RRI Kendari. Programme 4 RRI Kendari broadcast cultural programs from main ethnic groups in Southeast Sulawesi: Tolaki, Buton, Muna, Moronene, Bugis, Makassar, Bajo, Java, Sunda, and Bali. However, the cultural programs in Programme 4 RRI Kendari not only serve as a means for accommodation toward various ethnic groups in Southeast Sulawesi, but contestation is also happened among themselves in these cultural programs. Before they are broadcasted in Programme 4, these cultural programs were broadcasted in Programme 1, which has wider range and has more complete facilities, including interactive facility. Meanwhile, as a new channel, Programme 4 do not have wide range of broadcasting capacity as in Programme 1, and its facilities are still limited. The limitation of Programme 4 facilities makes various ethnic groups in Southeast Sulawesi feel no longer accommodated in cultural programs of RRI Kendari as it was broadcasted in Programme 1 before.